Cystic lung tuberculosis in children: A series of five cases - Chetna Mishra; Pooja Abbey; Rama Anand; Varinder Singh; Ravinder Kaur (South African Journal of Radiology, 2023)
Frequent imaging manifestations of pulmonary tuberculosis are airspace or interstitial nodules with or without tree-in-bud nodules, consolidation, cavitation, ground glass opacity, miliary nodules, lymphadenopathy and pleural effusion. It is unusual to encounter cystic changes in patients with pulmonary tuberculosis, and these findings should be differentiated from other cystic lung diseases. This case series describes five cases of cystic lung disease in children with tuberculosis (TB) with illustrative chest radiography and CT findings.